The Sign, Linguistic Analysis, Idioethnic Interpretation of Communication and Linguistic Persona - Mikhailovna Buzinova, Liudmila; Petrovich Sedykh, Arkadiy; Sergeevna Tsvetova, Natalya; Vladimirovna Bakirova, Natalia; Nikiforovich Kovalenko, Boris (International Journal of Engineering and Technology, 2018)
The purpose of the article is to review the theoretical aspects of ethnocultural interpretation of communicative behavior as a part of the national linguistic identity. Logical-semantic and logical-communicative components of an utterance are reviewed regarding the identification of ethnocultural components of an utterance.Such categories as sentence, modus, and dictum are regarded as phenomena that are characterized by their ethnocultural parameters. A sentence-utterance performs a semiotic function that unites denotative and significative meanings. The significative meaning of a linguistic sign is understood as the internal form of a new meaning. The internal form as a vector of asymmetrical features induces national means of actualization of a sentence, modus, and dictum.The authors propose to identify and study the specific features of idioethnic correlations among a sentence, modus, and a dictum within cognitive motivations in order to achieve the communicative purpose of a speech act. It is stated that the unique character of an utterance does not exclude idiolect means of its realizations within the framework of using preferable forms of modality and narrative formats in national languages.The prospects of studying the basics of the linguistic analysis and the idio-ethnic interpretation of sign structures are viewed within the framework of the comprehensive analysis of discourse and communication based on the interdisciplinary approach. It seems to be possible to single out additional parameters of the sign and communication of any type by using this method. The basic elements of the communicative structure of a speech act are reviewed.Â Â